1986
DOI: 10.1007/bf00398696
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of cyclic organochlorines in the marine environment

Abstract: Cyclic organochlorines are highly hydrophobic chemicals which usually possess a high persistence to microbial breakdown. These behavioural aspects determine the suitability of each environmental compartment for monitoring purposes, which is discussed.It is concluded, that monitoring of (cyclic) organochlorines should only be executed for compounds about which solid information is available on their environmental behaviour in abiotic and biotic environmental compartments. Under these conditions benthic inverteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Before their production and usage had been banned in many countries in the 1970s, mixtures of different PCBs (i.e., Aroclor in Europe and the USA, Sovol in the former USSR) were used extensively for cooling-agent manufacture, for capacitors and transformers, as hydraulic fluids, paint additives, and in manufacturing carbonless copy paper (Boon and Duinker, 1986;Okay et al, 2009;UNEP, 2003). PAHs originate primarily from the incomplete combustion of fossil fuels and biomass (pyrolitic PAHs), slow maturation of organic matter (petrogenic PAHs), and the short-term degradation of organic matter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before their production and usage had been banned in many countries in the 1970s, mixtures of different PCBs (i.e., Aroclor in Europe and the USA, Sovol in the former USSR) were used extensively for cooling-agent manufacture, for capacitors and transformers, as hydraulic fluids, paint additives, and in manufacturing carbonless copy paper (Boon and Duinker, 1986;Okay et al, 2009;UNEP, 2003). PAHs originate primarily from the incomplete combustion of fossil fuels and biomass (pyrolitic PAHs), slow maturation of organic matter (petrogenic PAHs), and the short-term degradation of organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…The genus is used widely in international monitoring programs (e.g., Mussel Watch in the USA, RNO in France) because of its broad distribution, sedentary life mode, high tolerance to a wide range of environmental conditions, and the ability of accumulating chemicals in their tissues in concentrations proportional to levels in the external environment (Goldberg et al, 1978;Phillips, 1978;Webster et al, 2006). Previous studies have indicated that concentrations of PCBs and PAHs in mussels can vary throughout the year (Boon and Duinker, 1986;Hummel et al, 1990;Piccardo et al, 2001;Webster et al, 2006). Temporal fluctuations in the soft tissue concentrations of organic contaminants are linked directly to the availability of food, hydrological conditions, and internal factors such as physiological condition, age, size, and lipid content (Baumard et al, 1998;Boon and Duinker, 1986;Gilek et al, 1996;Gossiaux et al, 1996;Kuwabara et al, 1986;Widdows et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…However, such an interpretation can be based only on sound knowledge of the kinetics and toxicology of the contaminants and species concerned (cf. Adema et al, 1972;Boon, 1985;Boon & Duinker, 1986;Everaarts, 1986;Reijnders, 1986;De Wolf et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic regulation or transformation of the pollutants may occur, while interaction between pollutants may influence the uptake (Phillips & Segar, 1986;Bryan, 1980;Bryan et al, 1980;Boon & Duinker, 1986). Furthermore, biological factors, such as body composition, sex, age, size, sexual cycle and feeding habits, influence the concentrations of contaminants in biota (Harms & Kerkhoff, 1988;Kruse & Kriiger, 1984;Gordon et al, 1980).…”
Section: Monitoring In Biotamentioning
confidence: 99%
“…A further improvement may be attained by normalizing the concentrations to a parameter characteristic for the phase which is (estimated to be) important for the uptake. For hpophilic organic compounds such as chlorobipheriyls and polycychc aromatic hydrocarbons, the hpid content of the tissue is an often applied parameter, concentrations being expressed on hpid basis (Boon & Duinker, 1986;Bruggeman, 1982). Recently, it has been shown that the fat content of cod liver significantly influences the accumulation of a number of heavy metals (Grimes et al, 1985).…”
Section: Monitoring In Biotamentioning
confidence: 99%